A New Species of Pseudocyclopiidae (Crustacea, Copepoda, Calanoida) From an Anchialine Environment of South-Eastern Italy - Belmonte, Genuario (Frontiers in Ecology and Evolution, 2022)
A new species of stygobiont copepod (Stygocyclopia badinoi sp.nov.) is described from the anchialine environment of Zinzulùsa cave (Catro, Italy). It is the first Pseudocyclopiidae (Copepoda, Calanoida) to be reported from Italian fauna, and the second one reported from the Mediterranean area. The current species is characterized by the largest body sizes among congeners, and by a general lacking of spiny fields on the cuticle of Urosome and P5. The genus has representatives in anchialine environments of coastal caves in Australia, New Caledonia, Philippines, Canaries and Balearic islands, and the present Mediterranean report is a relict station well included in the frame of an ancient and widespread geographic distribution of ancestral Pseudocyclopiidae along the Tethys Ocean coastlines.